Clinical characteristics associated with the properties of gut microbiota in peritoneal dialysis patients. Issue 3 (May 2021) - Jiang, Na; Zhang, Chenhong; Feng, Hao; Yuan, Jiangzi; Ding, Li; Fang, Wei; Gu, Aiping; Huang, Jiaying; Li, Na; Gu, Leyi; Ni, Zhaohui; Mou, Shan
Background: Gut microbiota alters in patients with end-stage renal disease, which contributes to inflammation, atherosclerosis, and results in increased incidence of cardiovascular diseases. The present study investigated the potential clinical factors, which influence the gut microbial structure and function in patients undergoing peritoneal dialysis (PD). Methods: This is a cross-sectional study performed in 81 prevalent PD patients. Gut microbiota was assessed by high throughput sequencing of 16S ribosomal ribonucleic acid gene in fecal samples. Gas chromatography was conducted to measure stool short-chain fat acid (SCFA) concentrations. Demographic parameters and clinical characteristics, including dialysis regimen, residual renal function, nutrition, and inflammation, were retrieved and related to the properties of gut microbiota. Results: PD duration, peritoneal glucose exposure, and estimated glomerulus filtration rate (eGFR) were identified to be associated with microbial variations. Significant separation of microbial composition was shown between patients with short or long PD duration ( p = 0.015) and marginal differences were found between patients grouped by different levels of peritoneal glucose exposure ( p = 0.056) or residual renal function ( p = 0.063). A couple of gut bacteria showed different abundance at amplicon sequencing variant level between these patient groups ( p < 0.05). In addition, stool isobutyric and isovaleric acid concentrations were significantly reduced in patients with longer dialysis duration, higher peritoneal glucose exposure, or declined eGFR ( p < 0.05). Conclusions: This pilot study demonstrated that long dialysis duration, high peritoneal glucose exposure, and loss of residual renal function were associated with gut microbiota alteration and reduced branched-chain SCFA production in PD patients.